IMPLEMENTASI MANAJEMEN BISNIS SYARI’AH UNTUK PENINGKATAN VOLUME PENJUALAN DI KANTIN 1 PUTERA UD. ASSYARIF PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Misbahul Ali; Himawan Pradipta; Syarifuddin (Al-Idarah, 2022)
The canteen is a place in the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo that provides the basic needs of students, in the form of food and drinks every day, so that every day there must be buying and selling interactions carried out by students and canteen employees. There are several products offered by the canteen in providing facilities for the basic needs of the students, namely rice, ice, cakes, young coconut, herbal herbs and instant noodles. In increasing the sales volume of the canteen, do the best possible service so that consumers can feel satisfied. One of the management applied by the canteen in increasing sales volume is by facilitating all the basic needs of students. In addition, the canteen also provides excellent service by building the best possible chemistry in order to create comfort and compatibility so that sales volume also increases. In this paper it is concluded that the application of sharia business management to increase sales volume aims to satisfy santri consumers as consumers, so that the canteen gives students flexibility in choosing food. This can attract consumers to make repeat purchases at the canteen